The Behavior-Attitude Relationship and Satisfaction in Proenvironmental Behavior. Issue 9 (November 2019) - Ertz, Myriam; Sarigöllü, Emine
Past research on environmentally sustainable behaviors has focused on the impact of a wide array of psychological factors, such as values, attitudes, norms, motivation, or perceptions, on behavior. The aim of this article is to study an alternative perspective by focusing on the effect of behavior on attitude, instead of the opposite, and by examining the mediation of satisfaction on that relationship. Drawing on both the self-perception and cognitive dissonance theories, we demonstrate that the expectancy disconfirmation model illuminates the conditions under which the past behavior-attitude link may improve. An online study with 409 U.S. citizens revealed that satisfaction mediates the positive behavior-attitude relationship, while this is not the case for the attitude-behavior relation. Our results also highlight the importance of multidimensional conceptualization for both proenvironmental behavior (PEB) and attitudes toward PEB, while providing useful guidelines for practitioners and policy makers.